2020
DOI: 10.3390/microorganisms8111650
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus thermophiles DMST-H2 Promotes Recovery in Mice with Antibiotic-Associated Diarrhea

Abstract: Antibiotic-associated diarrhea (AAD) is the most common side effect of antibiotics and is routinely treated with probiotics in clinical. Streptococcus thermophiles, extensively utilized for producing dairy foods, has recently been regarded as a new promising probiotic candidate. In this study, the efficacy of Streptococcus thermophiles DMST-H2 (DMST-H2) for AAD treatment in mice was investigated. DMST-H2 was isolated from Chinese traditional yogurt, proved to be non-toxic, and presented tolerance against simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…39 Streptococcus thermophiles DMST-H2 relieved inflammation by reducing TNF-α, increasing IL-10 and IFN-γ. 40 In addition, some probiotics have been demonstrated to be effective in activating anti-inflammatory mechanisms and accommodating mucosal immune responses. 41 For example, L. casei DN-114001 restrains the NF-κB signal transduction pathway and ultimately reduces the pathogenic activation of the pro-inflammatory signal transduction cascade.…”
Section: Discussionmentioning
confidence: 99%
“…39 Streptococcus thermophiles DMST-H2 relieved inflammation by reducing TNF-α, increasing IL-10 and IFN-γ. 40 In addition, some probiotics have been demonstrated to be effective in activating anti-inflammatory mechanisms and accommodating mucosal immune responses. 41 For example, L. casei DN-114001 restrains the NF-κB signal transduction pathway and ultimately reduces the pathogenic activation of the pro-inflammatory signal transduction cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lactobacillus strains reduced the level of TNF‐α in an LPS‐stimulated mouse model (Reyes‐Díaz et al., 2018). Streptococcus thermophiles is a new promising probiotic candidate that promotes the recovery in mice with antibiotic‐associated diarrhea and reduces the levels of proinflammatory cytokines (TNF‐α) (Hu et al., 2020). These results confirm that anti‐inflammatory effect of CLB is due to a reduction in the level of TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response of the body is usually caused by the imbalance of cytokines ( 32 ), among which interleukin (IL) and tumor necrosis factor (TNF) play an important role in the immune system as communication factors between immune cells, which can reflect the inflammatory status of the host ( 33 ). Studies have shown that AAD is always accompanied by systemic inflammation, showing an increase in proinflammatory cytokines and a decrease in anti-inflammatory cytokines ( 34 ). In the model group of this study, the levels of anti-inflammatory cytokines such as IL-4 and IL-10 decreased significantly, whereas the levels of proinflammatory cytokines such as TNF-α and IFN-γ increased significantly ( p < 0.05), which finally led to the increase of inflammatory cytokines in AAD mice, further demonstrating the successful establishment of AAD mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Because the intestinal flora is considered to be an organ that helps to regulate the metabolism of the host, the change of intestinal flora leads to the change of metabolic pathway, and the most obvious one is that the amino acid metabolism will obviously increase in AAD mice ( 34 ). Moreover, amino acid can enhance cell metabolism, increase the synthesis of protein by regulating protein translation, and increase the content of mitochondria in skeletal muscle and adipocytes, which is essential to maintain normal physiological internal environment balance ( 56 ).…”
Section: Discussionmentioning
confidence: 99%